Total Quality Marketing Training to Enhance Value-Added for Red Brick Business in Kesik Village, East Lombok - Iwan Kusmayadi; Djoko Suprayetno; Laila Wardani; Muhammad Ahyar (Unram Journal of Community Service, 2024)
The target audience for this activity is the owners of red brick craft businesses in Kesik Village, Masbagik District, East Lombok. This activity will equip business operators with concrete and applicable strategies and models related to innovative business governance and suitable for the creative industry. The PPM team will pay special attention to marketing aspects based on Total Quality Management (TQM). Integrating TQM into marketing functions, Total Quality Marketing is crucial for a company, including small industries, to develop the structure and value-added of the business. Total Quality Marketing will ensure companies to focus on the market, thereby continuously improving business processes to respond to rapid changes from the market and customers